Xylella Fastidiosa Diseases and Their Leafhopper Vectors - Russell F. Mizell; Peter C. Andersen; Christopher Tipping; Brent Brodbeck (EDIS, 2004)
As its name implies, Xylella fastidiosa is a fastidious (hard to culture), bacterium that resides in the plant xylem tissue. It is vectored (spread) almost exclusively by xylem feeding leafhoppers. Strains of this bacterium are the causal agent of phony peach disease (PPD), plum leaf scald, Pierce's disease (PD) of grapes, citrus variegated chlorosis (CVC), and leaf scorch of almond, coffee, elm, oak, oleander pear, and sycamore. Diseases caused by X.Fastidiosa are most prevalent in the southeastern United States, but may also occur in California, southern Ontario, and the southern midwestern states. This document is ENY-683, one of a series of the Department of Entomology and Nematology, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: October 2003.